The Influence of Teaching Style and Motivation Level on Increasing Learning Outcomes Table Tennis Skills - Agy Fhandu Awally; Ayi Suherman; Herman Subarjah (Universitas PGRI Palembang, 2023)
The purpose of this study was to determine the teaching style of the individual program and guided discovery of the learning outcomes of table tennis skills with the level of sports motivation. This study used a 2x2 factorial design with a sample of 32 students who were divided into four groups so that each group consisted of 8 samples. The sampling technique used in this study was purposive sampling and matching paired techniques. The results showed that there was an influence of individual program teaching style and guided discovery on table tennis skills learning outcomes, then there was an interaction between individual program teaching styles and guided discovery with the level of sports motivation on table tennis skills learning outcomes. The individual program teaching style is better used than the guided discovery teaching style to improve table tennis skills learning outcomes in the high motivation group, while the guided discovery teaching style is better used than the individual program teaching style to improve table tennis skills learning outcomes in the low motivation group.